Efektivitas Lidah Buaya (Aloe Vera) Terhadap Penurunan Kadar Glukosa Darah Pada Penderita Diabetes Melitus Tipe II: Literature Review - Nabila Mardiana; Hidayat Turochman (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2025)
Background: Diabetes Mellitus (DM) is an increase in blood glucose levels accompanied by various metabolic disorders due to hormonal disorders. Diabetes mellitus is caused by the pancreas that cannot produce insulin or insulin resistance, so that blood glucose levels increase. Increased blood glucose levels can damage blood vessels and nerves, especially in the hands and feet. To overcome increased blood glucose levels and prevent complications, management is needed that can help lower blood glucose levels. Aloe vera contains micronutrients that can help improve blood glucose control in the body and chromium which plays an important role in preventing complications for people with diabetes mellitus. Aim: To determine the effectiveness of aloe vera on reducing blood glucose levels in people with type II diabetes mellitus. Method: The search strategy was carried out through Google Scholar. The research method used was a literature review with a total of five articles. Results of the study: Based on all the findings, aloe vera decoction has been shown to be more effective in lowering blood glucose levels in people with type II diabetes mellitus compared to just boiled water on aloe vera or aloe vera juice. Conclusion: Aloe vera decoction has been shown to be effective in lowering blood glucose levels in people with type II diabetes mellitus. Keywords: Diabetes mellitus type II, Blood glucose levels, Aloe vera